Effect of Zhan Zhuang Qigong on upper limb static tremor and aerobic exercise capacity in patients with mild-to-moderate Parkinson's disease: study protocol for a randomised controlled trial. Issue 7 (12th July 2022) - Zhang, Linlin; Liu, Xihua; Xi, Xiaoming; Chen, Yuxiao; Wang, Qing; Qu, Xinjie; Cao, Haihao; Wang, Limin; Sun, Wenyu; Chen, Guoming; Liu, Huifen; Jiang, Xiaoyu; et al.
Abstract : Introduction: Currently, the first choice for the clinical treatment of static tremor in Parkinson's disease (PD) is drug therapy, however side effects are common. In recent years, the effects of physical therapy on PD has become a serious research focus. Studies have indicated that aerobic and resistance exercises alleviate PD movement disorders and improve aerobic capacity, but the effects of Qigong on PD static tremor and aerobic capacity remain unknown. Methods and analysis: Objective: To observe the effects of Zhan Zhuang Qigong on upper limb static tremor and aerobic capacity in patients with PD, we established a rigorous randomised, parallel-controlled, assignment hidden, evaluator-blinded protocol. Methods: Seventy-two patients with PD, at the Affiliated Hospital of Shandong University of Traditional Chinese Medicine, were recruited and randomly divided into a control (n=36) and experimental group (n=36). The intervention group received conventional medicine plus Zhan Zhuang Qigong exercises five times a week at 30 min each time, over an 8-week period. The long-term effects of Zhan Zhuang Qigong on PD was investigated after the intervention. Phyphox APP, CRST, CPET, UPDRS(II, III) were used to evaluate tremor, aerobic capacity, and motor function in groups. Discussion: We are investigating the effects of Zhan Zhuang Qigong on upper limb static tremor and aerobic capacity in patients with PD. If positive are identified, they will add a new research direction and evidence for the clinical exploration of exercise therapy for PD. Ethics and dissemination: This study was approved by the Ethics Committee of Shandong University of Traditional Chinese Medicine (Approval Number: 2021–025-KY). The Committee will be informed of any changes to the trial protocol, such as intervention intensity, outcome indicators and data collection. Study results will be presented as a paper at an international conference or in a journal. Trial registration number: ChiCTR2100053529.